Α, β-Diaryl unsaturated ketones via palladium-catalyzed ring-opening of cyclopropenones with organoboronic acids. Issue 10 (4th April 2018) - Shan, Lidong; Wu, Ge; Liu, Miaochang; Gao, Wenxia; Ding, Jinchang; Huang, Xiaobo; Wu, Huayue
Abstract : Palladium-catalyzed ring-opening acylation of cyclopropenones with organoboronic acids (aryl and vinylboronic acids) at room temperature has been developed to synthesise α, β-diaryl unsaturated ketones with good yields and excellent stereospecificity. Abstract : Palladium-catalyzed ring-opening acylation of cyclopropenones with organoboronic acids at room temperature has been developed. Both arylboronic acids and vinylboronic acids are viable in this acylation reaction, providing a new protocol to synthesise α, β-diaryl unsaturated ketones with good yields and excellent stereospecificity. Preliminary mechanistic studies indicated that a vinylpalladium intermediate was generated in this procedure.